Effects of yawed inflow on the aerodynamic and aeroacoustic performance of ducted wind turbines. Issue 201 (June 2020) - Dighe, Vinit V.; Avallone, Francesco; van Bussel, Gerard
Abstract: Ducted Wind Turbines (DWTs) can be used for energy harvesting in urban areas where non-uniform inflows might be the cause of aerodynamic and acoustic performance degradation. For this reason, an aerodynamic and aeroacoustic analysis of DWTs in yawed inflow condition is performed for two duct geometries: a baseline commercial DWT model, DonQi®, and one with a duct having a higher cross-section camber with respect to the baseline, named DonQi D5. The latter has been obtained from a previous optimization study. A numerical investigation using Lattice-Boltzmann Very-Large-Eddy Simulations is presented. Data confirm that the aerodynamic performance improvement, i.e. increase of the power coefficient, is proportional to the increase of the duct thrust force coefficient. It is found that, placing the DWT at a yaw angle of 7.5°, the aerodynamic performances of the DonQi D5 DWT model are less affected by the yaw angle. On the other hand, this configuration shows an increase of broadband noise with respect to the baseline DonQi® one, both in non-yawed and yawed inflow conditions. This is associated to turbulent boundary layer trailing edge noise due to the turbulent flow structures developing along the surface of the duct.